Dental implant surgery: a concise review of the literature / Fatimah Al Khateeb, Hazmyr Abdul Wahab and Tan Su Keng - Al Khatee, Fatimah; Abdul Wahab, Hazmyr; Tan, Su Keng (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
Edentulism is a global challenge affecting patients’ psychosocial wellbeing, now well-treated by dental implants. Due to the advancement in the field of oral implantology, there is a plethora of surgical techniques and protocols at the disposal of clinicians, backed by an ever-divided body of research. Treatment with dental implants has become ever more sought after because of their high survival and success rates and increased affordability. In turn, this has put increased demand on clinicians who owe their patients the highest standard of care backed by sound scientific evidence. However, dentists are expressing concern over ambiguous dental implant guidelines and protocols. Implant survival, success and failure rates have been reported differently for various modalities and justified differently in various research. This lack of consensus appears to stem from erroneous or non-standardized study designs, yielding inconsistent results. Therefore, correctly designed and well-reported high-level studies are needed to aid clinicians in treatment decision-making.